Enhancement of peak and mean power in concentric phase of resistance exercises - Zemková, Erika; Jeleň, Michal N; Kováčiková, Zuzana C; Ollé, Gábor; Vilman, Tomáš S; Hamar, Dušan S (Journal of strength and conditioning research, 2014)
The study compares the differences in peak and mean power of concentric-only and countermovement resistance exercises (ΔP) with different weights. A group of 27 fit men randomly performed 3 repetitions of either barbell bench presses or barbell squats on different days. The initial weight of 20 kg was increased by 10 or 5 kg (at higher loads) up to at least 85% of a previously established 1 repetition maximum (1RM). A computer-based system FiTRO Dyne Premium was used to monitor force and velocity and to calculate power. The peak values and mean values of power during the entire concentric phase of lifting and during the acceleration phase were analyzed. Results showed that maximal ΔP calculated from the peak and mean values in the acceleration phase of bench presses was achieved at lower weights (118.4 ± 19.0 W at 47% of 1RM and 116.2 ± 15.3 W at 48% of 1RM, respectively) than the one calculated from mean values in the entire concentric phase of lifting (114.8 ± 14.8 W at 57% 1RM). Likewise, maximal ΔP calculated from the peak and mean values in the acceleration phase of squats was achieved at lower weights (127.7 ± 20.4 W at 67% of 1RM and 124.3 ± 22.1 W at 69% of 1RM, respectively) than the one calculated from the mean values in the entire concentric phase of lifting (125.0 ± 19.2 W at 77% of 1RM). This fact has to be taken into account when training efficiency is evaluated, namely, in sports requiring the production of maximal force in a short time.
Keywords: dospělí; kosterní svaly; Weight Lifting; zátěžový test; Adult; mladý dospělý; Resistance Training; svalová síla; lidé; Muscle, Skeletal; Muscle Strength; biomechanika; Acceleration; náhodné rozdělení; Male; Exercise Test; Young Adult; ergometrie; vzpírání; Ergometry; Random Allocation; zrychlení; mužské pohlaví; odporový trénink; Biomechanical Phenomena; Humans